(untitled) (Research, Society and Development, 2024)
Objectives: To map the existing scientific evidence on the use of echocardiography with speckle tracking technique in pregnant women with preeclampsia. Methodology: This protocol will follow the methodological recommendations proposed by the Joanna Briggs Institute (JBI) Evidence Synthesis Manual, has been registered in the Open Science Framework, and was developed according to the Preferred Reporting Items for Systematic Review and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) Checklist and Explanation. The search for studies of interest will be conducted in databases such as PubMed, EMBASE, Cochrane Library, Web of Science, BVS, and grey literature investigation will occur on Google Scholar. Findings will be exported to the Mendeley reference manager and subsequently to the Rayyan Software where the selection of studies will be performed by two independent reviewers, according to the inclusion criteria. Data will be extracted using a form developed by the authors and will be displayed through tables, figures, and/or graphs and analyzed descriptively. Results: This scoping review on the use of echocardiography with speckle tracking technique in pregnant women with preeclampsia aims to synthesize such knowledge. Conclusion: To disseminate and expand the indications of this diagnostic method, enabling the identification of gaps in the literature for future research on the topic contributing to the surveillance of maternal cardiovascular health.